Eletrodeposição de nanoestruturas de cobalto em alumina anódica porosa e sua caracterização magnética - Oliveira, Cristiane Pontes de (Universidade Federal de São Carlos, 2009)
In this thesis, the results regarding the investigation about the cobalt electrodeposition in templates of porous anodic alumina are presented. The doctorade is divided in four main sections. The _rst one has consisted in exploring many experimental set up to the preparation of porous anodic alumina using galvanostatic mode. The main results are related to the high ordering achieved using the galvanostatic mode and the sistem versatility concerning preparation of new architectures in porous anodic alumina such as the two overlapped porous layers presented in this thesis. The second part is about the computational study of the metalic electrodeposition in porous templates. In this step a bidimensional model to the metal electrodeposition in porous sistem was developed and simulated. The model considers one potenciostatic pulse. Potential distribution inside the template is calculated using the Laplace equation. Difusion equation takes into account the transport of electroactive species. Simulations show clearly the interaction between the concentration gradient inside the pore and potential distribution in the oxide inner. This dynamic allows to understand the top deposition and is consistent with the catch up e_ect. Based on insights from early step, the cobalt electrodeposits in porous anodic alumina were prepared by galvanostatic and potentiostatic pulsed electrodeposition. Finaly, the fourth part of the work deal with the magnetic characterization of the cobalt electrodeposits. The electrodeposits prepared by galvanostatic pulsed electrodeposition presented the exchange bias behaviour. The exchange bias is result of the presence of antiferromagnetic cobalt oxide, which lead to the formation of ferromagnetic (Co)/antiferromagnetic (CoO) interfaces responsible by the increase in the coercive _eld when the sample is cooled at presence of high magnetic _eld (Field Cooling procedure - FC). In addition, it was observed a anomalous temperature dependence of coercive _eld. Regarding the electrodeposits prepared by potentiostatic pulsed electrodeposition, they showed similar temperature dependence of coercive _eld. The coercive _eld (HC1) increase as the temperature is reduced from 300 K, achieving a maximum around 100 K, and from this point, the coercive _eld decrease signi_cantly. According to the reversible magnetic susceptibility behaviour, this result is related to the magnetoelastic contribution to the sistem anisotropy.
Electrodeposition of cobalt nanostructures in porous anodic alumina and their magnetic characterization
Keywords: Eletroquímica; Anodização; Eletrodeposição; Simulação computacional; Magnetismo; Nanofios; CIENCIAS EXATAS E DA TERRA::QUIMICA